Assessment of whole brain white matter integrity in youths and young adults with a family history of substance‐use disorders. Issue 11 (27th May 2014) - Acheson, Ashley; Wijtenburg, S. Andrea; Rowland, Laura M.; Winkler, Anderson M.; Gaston, Frank; Mathias, Charles W.; Fox, Peter T.; Lovallo, William R.; Wright, Susan N.; Hong, L. Elliot; Dougherty, Donald M.; Kochunov, Peter
Abstract Individuals with a family history of substance use disorders (FH+) are at a greater risk of developing substance use disorders than their peers with no such family histories (FH−) and this vulnerability is proportional to the number of affected relatives (FH density). The risk for developing substance use disorders peaks during adolescence to early adulthood in the general population, and that is thought to be related to delayed maturation of frontocortical and frontostriatal functional circuits. We hypothesized that FH+ youth and young adults have impaired myelination of frontocortical and frontostriatal white matter tracts. We examined fractional anisotropy (FA) data in 80 FH+ and 34 FH− youths (12.9 ± 1.0 years) and in 25 FH+ and 30 FH− young adults (24.3 ± 3.4 years). FH+ youths had lower FA values in both frontocortical and frontostriatal tracts as well as parietocortical tracts including the anterior, superior and posterior corona radiata and the superior frontal‐occipital fasciculus. Moreover, FA values in these tracts were negatively correlated with FH density. FH+ adults had lower FA values in two frontocortical tracts: the genu of the corpus callosum and anterior corona radiata and also significant negative correlations between FA and FH density in these same tracts. In both groups, lower FA values corresponded to higher radial diffusivity suggesting reduced axonal myelination. We interpreted our findings as evidence for impaired myelination of frontal white matter that was proportional to FH density. Our data suggest that deficits may partially resolve with age, paralleling an age‐related decline in risk for developing substance use disorders. Hum Brain Mapp 35:5401–5413, 2014. © 2014 Wiley Periodicals, Inc.